(3GdeNJGQ ef TYQ CHj GdWjH GdeJfHjs - (3CMeO Hf GdMSjf Hf GdMSf Hf YHO GdUeO GdcfOj GdeJfHj, CHh GdWjH,J (B254 (3g` s
(3ChdgG (B:s
(3eHJhQ GdChd , hChd eG ajg (B: (3aOi dc ef jbUQ Yf eOGcG adGedc EPG ZdG aOGcG s
(3BNQgG (B:s
(3hgHc SeMJ MJi dGLhGO acja YdhJ MJi dGQajYkG s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B4s
(3HgG fXGe GdJYbjHIs
(3OjhGf TYQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B111 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B1 - (3U (B201 ; (3gOjI GdYGQajf ddHZOGOi(B: (3L (B1 - (3U (B64s
(3JHUQGJ GdCUd (B:s
(3GdfSNI fGbUI GdChd s
Keywords: (3GdCOHs